2016
DOI: 10.1038/srep30489
|View full text |Cite
|
Sign up to set email alerts
|

SOX9 is a novel cancer stem cell marker surrogated by osteopontin in human hepatocellular carcinoma

Abstract: The current lack of cancer stem cell (CSC) markers that are easily evaluated by blood samples prevents the establishment of new therapeutic strategies in hepatocellular carcinoma (HCC). Herein, we examined whether sex determining region Y-box 9 (SOX9) represents a new CSC marker, and whether osteopontin (OPN) can be used as a surrogate marker of SOX9 in HCC. In HCC cell lines transfected with a SOX9 promoter-driven enhanced green fluorescence protein gene, FACS-isolated SOX9+ cells were capable of self-renewal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 54 publications
(61 reference statements)
5
54
0
1
Order By: Relevance
“…E2F8, which belongs to the E2F transcriptional factor family, promotes cell proliferation via regulating cyclin D1 expression in HCC . Sox9, a Notch1 classical downstream target, can promote cancer cell proliferation by promoting the expression of cyclin D1 . Cyclin D1 can form a complex with CDK4 or CDK6, which promotes cell cycle progression from G1‐phase to S‐phase , a phenomenon that was consistent with our results (see supplementary material, Figure S5B).…”
Section: Discussionsupporting
confidence: 90%
“…E2F8, which belongs to the E2F transcriptional factor family, promotes cell proliferation via regulating cyclin D1 expression in HCC . Sox9, a Notch1 classical downstream target, can promote cancer cell proliferation by promoting the expression of cyclin D1 . Cyclin D1 can form a complex with CDK4 or CDK6, which promotes cell cycle progression from G1‐phase to S‐phase , a phenomenon that was consistent with our results (see supplementary material, Figure S5B).…”
Section: Discussionsupporting
confidence: 90%
“…NWD1 might also be involved in cell division; a previous study showed that NWD1 expression levels positively correlate with the malignancy and tumor progression of human prostate cancer, and that the expression of NWD1 mRNA is upregulated by the transcription factor SOX9 in human prostate cancer cell lines, as mentioned above (Correa et al, ). Sox9, a member of the SRY (sex‐determining region Y) family of transcription factors, has been implicated in the maintenance of the stem cell pool in various organs (Kawai et al, ; Kiefer, ; Pritchett, Athwal, Roberts, Hanley, & Hanley, ). Sox9 is expressed in neural stem cells of different CNS regions, and is indispensable for their establishment and maintenance (Scott et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The study presented by Kawai et al provided experimental evidence on the role of SOX9 as a novel CSC marker [47]. Authors performed a number of experiments on isolated SOX9(+) cells and found that they are able to self-renew and differentiate into SOX9(-) cells.…”
Section: New Drugs and Shorter Treatment Durationmentioning
confidence: 97%